Granulated Silica Method for the Fiber Preform Production - Sönke Pilz; Hossein Najafi; Manuel Ryser; Valerio Romano (Fibers, 2017)
During the past few years, we have studied the granulated silica method as a versatile and cost effective way of fiber preform production and the sol-gel method. Until now, we have used the sol-gel technology together with an iterative re-melting and milling step in order to produce rare earth or transition metal doped granular material for the granulated silica method. Here, we present that the iterative re-melting (laser-assisted) and milling step is no longer needed to reach a high homogeneity. The sol-gel method also offers a high degree of compositional flexibility with respect to dopants; it further facilitates achieving high concentrations, even in cases when several dopants are used. We employed optical active doped sol-gel derived granulate for the fiber core, whereas pure or index-raised granulated silica has been employed for the cladding. Based on the powder-in-tube technique, where silica glass tubes are appropriately filled with these granular materials, fibers has been directly drawn (“fiber rapid prototyping”), or eventually after an additional optional quality enhancing vitrification step. The powder-in-tube technique is also ideally suited for the preparation of microstructured optical fibers.